The paradox of safety between pastors and female congregants - Hundzukani P. Khosa-Nkatini; Jacob T. Mofokeng (Khazanah Theologia, 2022)
Gender-Based Violence (GBV) is a world concern; however, in South Africa it has been declared as a national crisis that is embedded in the social-cultural context and history of the country. One of the greatest challenges in South Africa is the high unemployment rate and the pressure to fit into society. Some of those unemployed South Africans go to church for prayers with the hope to get employed. Unemployed South Africans are vulnerable due to unemployment and pressure to fit in, and this is sometimes influenced by social media. Some pastors take advantage of these individuals either by asking them to plant a â€œseedâ€ (money) or taking advantaged of them sexually. Women, young and old are the most vulnerable in church, the pressure to get employment, to get married, to stay married, to have children etc. are the most common prayer requests from women in church. GBV in South Africa have been an ongoing investigation by various disciplines. One of the most difficult and sensitive realities to investigate is the existence of clergy who abuse women they are supposed to care for as caregivers. The Church has been in the front line in spearheading programms within it to deal with GBV but little to done are said about Pastors as perpetrators directly the problem of GBV has been further fueled by socio status, poverty, gender and equality issues, African culture, long-standing silence about a problem that undermines the very foundations of pastoral work and institutional Christianity: sexual abuse of women by pastors. The aim of this article to challenge theology and the church on how the cycle of perpetrators among pastors can be broken and what role can pastoral counsellorsâ€™ play regarding both victims and offenders to prevent history from repeating itself and assure female congregants of their safety in church, this study will use literature review.